2019
DOI: 10.1155/2019/9134280
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cardiovascular Risk in Children, Adolescents, and Young Adults with Type 1 Diabetes

Abstract: Cardiovascular risk and obesity are becoming major health issues among individuals with type 1 diabetes (T1D). The aim of this study was to evaluate cardiovascular risk factors and obesity in youth with T1D in Lithuania. Methods. 883 patients under 25 years of age with T1D for at least 6 months were investigated. Anthropometric parameters, blood pressure, and microvascular complications were evaluated, and the lipid profile and HbA1c were determined for all patients. Results. Study subjects’ mean HbA1c was 8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Detailed clinical assessment and examination of this cohort is described previously [16], brie y at the study entry, data on onset, duration and treatment of diabetes were collected, clinical examination included height (cm), weight (kg), waist circumference (cm) and body mass index (BMI) (kg/m 2 ). BMI values were converted to Z-scores and strati ed to 4 weight status groups: underweight, normal weight, overweight and obesity, using World Health Organization approach [17].…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Detailed clinical assessment and examination of this cohort is described previously [16], brie y at the study entry, data on onset, duration and treatment of diabetes were collected, clinical examination included height (cm), weight (kg), waist circumference (cm) and body mass index (BMI) (kg/m 2 ). BMI values were converted to Z-scores and strati ed to 4 weight status groups: underweight, normal weight, overweight and obesity, using World Health Organization approach [17].…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…[15][16][17] The disparity in frequency might partly be explained by the observed different cutoff points of lipid indices used in these various studies. [18] Furthermore, our estimate of 46.8% remains comparable to the rate recently reported among the general adult population within the studied region. [19] Following the categorization of patterns of lipid/lipoprotein abnormalities in the current study, abnormal high plasma Tg status was observed to be the most common isolated abnormality; seconded by isolated abnormal low plasma HDL-C fractions.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to what has been reported for the adult population whereby the female gender is associated with a lower CV risk in pre-menopausal period, data from recent literature reported similar CV risk rates in males and females [ 27 , 28 , 29 ]. Several modifiable CV risk factors are related to anthropometric measurements and metabolic control [ 30 ]. Increased BMI and waist circumference are described in children and adolescents with diabetes, while elevated levels of HbA1c are positively correlated with increased macrovascular complications [ 1 , 24 , 27 , 31 ].…”
Section: CV Risk Factors In Children and Adolescents With Diabetesmentioning
confidence: 99%
“…In youth with diabetes, a more atherogenic lipid profile directly correlates with glycated hemoglobin, fasting glucose, age, disease duration and the presence of insulin resistance. Many of the aforementioned factors may be associated with a reduced nitric oxide availability [ 30 , 41 , 42 , 43 , 44 ]. Finally, the role of smoking and alcohol as CV risk factors in adulthood is well known, even if their long-term effects in adolescents have not been clarified yet [ 45 ].…”
Section: CV Risk Factors In Children and Adolescents With Diabetesmentioning
confidence: 99%